1993
DOI: 10.1083/jcb.121.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for channeled diffusion of pre-mRNAs during nuclear RNA transport in metazoans.

Abstract: Abstract. We report studies using an enhanced experimental system to investigate organization of nuclear pre-mRNA metabolism. It is based on the powerful genetic system and polytene nuclei of Drosophila. We observe (at steady state) movement of a specific premRNA between its gene and the nuclear surface. This movement is isotropic, at rates consistent with diffusion and is restricted to a small nuclear subcompartment defined by exclusion from chromosome axes and the nucleolus. Bulk polyadenylated nuclear pre-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 60 publications
(88 reference statements)
9
86
1
Order By: Relevance
“…This idea is supported by observations that certain mRNAs exit from one side of the nucleus (8) and that, in yeast, many transcriptionally active gene loci are located near the nuclear periphery (9). By contrast, a number of other studies have found that mRNP complexes move quite freely within the nucleus (10)(11)(12)(13)(14)(15)(16). This view is supported by studies of the distribution of newly synthesized Balbiani ring RNA in the salivary gland cells of insects (11), fluorescence recovery after photobleaching and fluorescence correlation spectroscopy studies of probes that bind to the poly(A) tails of mRNAs (12)(13)(14)(15), and from single-particle analysis of mRNP complexes bound to GFP-linked proteins (16).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…This idea is supported by observations that certain mRNAs exit from one side of the nucleus (8) and that, in yeast, many transcriptionally active gene loci are located near the nuclear periphery (9). By contrast, a number of other studies have found that mRNP complexes move quite freely within the nucleus (10)(11)(12)(13)(14)(15)(16). This view is supported by studies of the distribution of newly synthesized Balbiani ring RNA in the salivary gland cells of insects (11), fluorescence recovery after photobleaching and fluorescence correlation spectroscopy studies of probes that bind to the poly(A) tails of mRNAs (12)(13)(14)(15), and from single-particle analysis of mRNP complexes bound to GFP-linked proteins (16).…”
supporting
confidence: 50%
“…The mRNA clusters were always present at the edge of a dense chromatin region. These chromatin-associated, immobile clusters of mRNA probably comprise nascent transcripts that are still attached to the gene via RNA polymerase, having not yet undergone the 3Ј-terminal processing events required for their release (10,25).…”
Section: Dispersal Of Mrnp Particles From the Sites Of Transcriptionmentioning
confidence: 99%
“…However, not all pre-mRNA sequences are processed cotranscriptionally and posttranscriptional splicing does occur (Zachar et al, 1993;Baurén and Wieslander, 1994;Wuarin and Schibler, 1994). Importantly, isolated pre-mRNAs from mammalian cells may contain both introns and poly(A) tails.…”
Section: Introductionmentioning
confidence: 99%
“…This localization has been somewhat perplexing, because speckles were also shown to contain stable, polyadenylated RNA species distinct in their behavior from most pre-mRNAs (for review, see Fakan 1994;Mattaj 1994). When sites of transcription and splicing have been examined using fluorescence in situ hybridization techniques, genes and the highest concentrations of unspliced pre-mRNA are coincident at the light microscopic level (Zachar et al 1993;Zhang et al 1994); however, endogenous intron-containing pre-mRNAs are not always concentrated within speckles (Zhang et al 1994;Xing et al 1995). This has led to the suggestion that speckles contain the highest concentrations of splicing factors--perhaps serving as storage or assembly sites--and that lower concentrations may be present where splicing occurs (Fakan et al 1984;Fakan 1994;Xing et al 1995;Huang and Spector 1996).…”
mentioning
confidence: 99%